Biomechanical analysis of judokas`throwing techniques: focus on the preparation phase - Hamaguchi, K.; Furukawa, T.; Takeuchi, S.; Sasakawa, Y.; Deguchi, T. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to compare the Judo throwing technique "uchimata" (inner thigh throw) between high and low skilled judoka during the preparation phase. Fourteen male judokas participated in this research. Kinematic data were collected using three-dimensional motion capture systems. During the analysis of the thrower's (tori's) angular velocity and the receiver's (uke's) angular momentum in the preparation phase, it was observed that high skilled judoka exhibited a strong positive correlation between the peak angular velocity of tori's leg and the peak angular momentum of the uke. Additionally, the peak value of the tori's centre of mass (COM) velocity in the front-back direction was significantly higher for high skilled judoka. These findings suggest that, for the effective execution of the uchimata technique, rapidly advancing towards the opponent is crucial.